Method development and validation for multi-class veterinary drugs determination in poultry feed using quechers-dspe-ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) / Ahmad Talhah Suhaimi - Suhaimi, Ahmad Talhah (2021)
The use of veterinary drugs has received global attention in recent years especially due to the development of antimicrobial drug resistance. It is essential that suitable methods of analysis are available to control this problem. A method for the determination of 31 veterinary drugs belonging to 9 different classes in chicken feed has been developed. The method was based on QuEChERS (quick, easy, cheap, effective, rugged, and safe) extraction equipped with d-SPE clean-up. The sample preparation included ultrasonicate the mixture of acetonitrile, methanol and McIlvaine buffer followed by phase separation with MgSO4:NaCl addition. The detection and quantification were performed using single analytical run by ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) operating in both positive and negative multiple reactions monitoring (MRM). Validation was performed in accordance with the international guidelines. Acceptable results regarding linearity of the method, limit of detection (LOD) and limit of quantification (LOQ) were achieved for 23 of 31 investigated substances. The LODs ranged from 0.05 mg/kg to 1.12 mg/kg and LOQs from 0.17 mg/kg to 3.74 mg/kg. Average analyte recoveries ranged from 83.7% to 109.9%. The relative standard deviation value for repeatability ranged from 0.43% to 9.91%. Based on matrix effect analysis, only six compound which are FTD, FZD, CBR, RPM, TBL, IPZ passed for quantification with standard solution calibration. The validation results demonstrate that the described LC-MS/MS method provides sensitive, repeatable and reliable for safety monitoring and controlling veterinary drug use in chicken feed.